Establishing the Framework for Fabrication of a Bioartificial Heart. Issue 4 (July 2015) - Tao, Ze-Wei; Mohamed, Mohamed; Hogan, Matthew; Salazar, Betsy; Patel, Nikita M.; Birla, Ravi K.
Abstract : There is a chronic shortage of donor hearts. The ability to fabricate complete bioartificial hearts (BAHs) may be an alternative solution. The current study describes a method to support the fabrication and culture of BAHs. Rat hearts were isolated and subjected to a detergent based decellularization protocol to remove all cellular components, leaving behind an intact extracellular matrix. Primary cardiac cells were isolated from neonatal rat hearts, and direct cell transplantation was used to populate the acellular scaffolds. Bioartificial hearts were maintained in a custom fabrication gravity fed perfusion culture system to support media delivery. The functional performance of BAHs was assessed based on left ventricle pressure and on electrocardiogram. Furthermore, BAHs were sectioned and stained for the whole heart cardiac tissue distribution and for cardiac molecules, such as α-actinin, cardiac troponin I, collagen type I, connexin 43, von Willebrand factor, and ki67. Bioartificial hearts replicated a partial subset of properties of natural rat hearts. The current study provided a method for fabrication of a BAH and revealed challenges toward BAH fabrication with functional performance metrics of natural mammalian hearts.